Carboxypeptidase S- and Carboxypeptidase Y-Deficient Mutants of Saccharomyces cerevisiae - Wolf, Dieter H. (1981)
A new carboxypeptidase (carboxypeptidase S) was found in a Saccharomyces cerevisiae strain lacking carboxypeptidase Y (D. H. Wolf and U. Weiser, Eur. J. Biochem. 73:553-556, 1977). Mutants devoid of carboxypeptidase S activity were isolated from a mutant strain that was also deficient in carboxypeptidase Y. Four mutants were analyzed in detail and fell into one complementation group. The defect segregated 2:2 in meiotic tetrads. Gene dosage experiments indicated that the mutation might reside in the structural gene of carboxypeptidase S. The absence of both enzymes, carboxypeptidases Y and S, did not affect mitotic growth. Ascopore formation was only slightly affected by the absence of both carboxypeptidases. Protein degradation under conditions of nutrient deprivation and under sporulation conditions showed no obvious alteration in the absence of carboxypeptidases Y and S. When a proteinase B mutation, which led to the absence of proteinase B activity and resulted in the partial reduction of sporulation, was introduced into a mutant lacking both carboxypeptidases, the ability of diploid cells to sporulate was nearly completely lost. Mutants lacking both carboxypeptidases were unable to grow on the dipeptide benzyloxycarbonylglycyl-l-leucine as a sole nitrogen source, which indicates an additional function for carboxypeptidases Y and S in supplying nutrients from exogenous peptides. Catabolite inactivation of fructose-1,6-bisphosphatase, cytoplasmic malate dehydrogenase, and phosphoenolpyruvate carboxykinase and inactivation of nicotin-amide adenine dinucleotide phosphate-dependent, glutamate dehydrogenase, events which have been proposed to involve proteolysis in vivo, were not dependent on the presence of carboxypeptidase Y and S. In a mutant lacking both carboxypeptidases, four new proteolytic enzymes with carboxypeptidase activity were detected.